Registration of 'AU‐1101' Peanut. Issue 1 (16th October 2012) - Chen, Charles Y.; Ernest Harvey, J.; Lamb, Marshall C.; Touchton, Joseph T.
Abstract : 'AU‐1101' (Reg. No. CV‐117, PI 661498) is a large‐seeded Virginia‐type peanut ( Arachis hypogaea L. subsp. hypogaea var. hypogaea ) with high yield and medium maturity, uniform pod size and shape, high grade, superior shelling characters, low oil content, normal oleic acid content, and good flavor. AU‐1101 was developed through pedigree selection. AU‐1101 was tested under the experimental designation Exp3‐1114 and was released by the Alabama Crop Improvement Association in 2011. AU‐1101 was tested by Auburn University and the USDA‐ARS National Peanut Research Laboratory in West Texas and the Uniform Peanut Performance Tests as a local option. AU‐1101 has an alternate branching pattern, a prostrate growth habit, and a high percentage of fancy pods and large virginia‐type seeds. It has an even distribution of 39% extra‐large kernels and 35% medium‐size kernels. The seeds have pink testa and the average weight of extra‐large kernels was 105 g per 100 seeds and of medium kernels, 72.1 g per 100 seeds. Approximately 82% of the pods graded as fancy.